2003
DOI: 10.1046/j.1365-2427.2003.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting ammonium uptake in streams – an inter‐biome perspective

Abstract: Summary 1. The Lotic Intersite Nitrogen eXperiment (LINX) was a coordinated study of the relationships between North American biomes and factors governing ammonium uptake in streams. Our objective was to relate inter‐biome variability of ammonium uptake to physical, chemical and biological processes. 2. Data were collected from 11 streams ranging from arctic to tropical and from desert to rainforest. Measurements at each site included physical, hydraulic and chemical characteristics, biological parameters, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
223
3
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 253 publications
(257 citation statements)
references
References 94 publications
25
223
3
6
Order By: Relevance
“…Biomass-specific uptake was calculated as total molar mass of 15 N tracer per m 2 of each compartment divided by mole frequency of 15 N to 14 N in the NO 3 -of the overlying stream water. Biological N demand was calculated for each stream according to the method and assumptions of Webster et al (2003). Autotrophic demand was calculated for each stream, based on GPP measurements from stream metabolism estimates.…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass-specific uptake was calculated as total molar mass of 15 N tracer per m 2 of each compartment divided by mole frequency of 15 N to 14 N in the NO 3 -of the overlying stream water. Biological N demand was calculated for each stream according to the method and assumptions of Webster et al (2003). Autotrophic demand was calculated for each stream, based on GPP measurements from stream metabolism estimates.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Heterotrophic N demand was then calculated using CR from the metabolism estimates (Webster et al 2003). CR was corrected for autotrophic respiration (30% of GPP) and nitrification (2 mol O 2 /mol N) to determine heterotrophic respiration.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…leaf decomposition) and autotrophic (i.e. algal growth) processes in streams (Elwood et al 1981;Tank & Dodds 2003). However, to our knowledge, few stream studies have demonstrated a link between whole-stream N uptake and dissolved phosphorus availability.…”
Section: Discussionmentioning
confidence: 94%
“…However, to our knowledge, few stream studies have demonstrated a link between whole-stream N uptake and dissolved phosphorus availability. Webster et al (2003) reported a negative relationship between stream nitrate uptake and streamwater N:P ratio but they also noted that relationship was not significant when data from one of their sites was excluded or when a rank correlation was performed. In terrestrial systems, phosphorus limitation has been shown to reduce NO 3 ( uptake in plants (Lee 1982;Rufty et al 1990) so it is likely that phosphorus availability could also influence NO 3 ( uptake by instream biota.…”
Section: Discussionmentioning
confidence: 99%
“…This "aha moment" in the historical origins of the LINX collaboration illustrates how scientific progress often results from the juxtaposition of tools and concepts from diverse fields (Fisher 1997). Subsequently, the LINX projects investigated spiraling of NH 4 + , NO 3 -, organic N, and gaseous forms of N. In all phases of this work, we tried to link our measurements with hydrologic foundations (e.g., N uptake length [S w ] linked with hydraulic retention, subsurface area, and hydraulic uptake length; Webster et al 2003).…”
Section: How the History Of Stream Ecology Laid The Groundwork For Sumentioning
confidence: 99%